English as a Means of Intercultural Communication in Ecotourism (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The English language plays a crucial role in intercultural communication within the field of ecotourism, serving as a bridge between local communities and international tourists. In an era of globalization, the ability to communicate effectively in English is essential for ecotourism professionals, including tour guides, park rangers, and local business owners. This paper explores the importance of English as a medium of intercultural exchange in ecotourism, highlighting its role in promoting sustainable tourism practices, fostering cross-cultural understanding, and enhancing the visitor experience. The study also examines the challenges faced by ecotourism professionals in Uzbekistan in acquiring and utilizing English proficiency in their daily interactions. By analyzing the current linguistic demands of the ecotourism sector, this research provides insights into effective language training methods that can improve communication skills and contribute to the sustainable development of ecotourism in Uzbekistan.